Tripulantes: una experiencia entre la educomunicación y las narrativas transmedia - Salazar Estrada, Maribel (Folios, revista de la Facultad de Comunicaciones y Filología, 2025)
Project created by the Facultad de Comunicación Audiovisual del Politécnico Colombiano Jaime Isaza Cadavid. This study focuses on ninth-grade students of the Institución Educativa San Fernando, at Amagá (Antioquia, Colombia), analyzing how transmedia narratives can promote educational equity and improve the mental health of participants. The research employs a qualitative approach, encouraging students to create content as an integral part of the process. Through five methodological phases (diagnosis, design, implementation, analysis, and final report), the project examines the potential of transmedia narratives to transform teaching and learning methods. Preliminary results indicate that these emerging narratives foster spaces for dialogue, creation, and participation in the educational environment. The research not only contributes to the field of transmedia narratives in education, but also offers perspectives for thebdevelopment of educommunicative strategies.